THE IMPACT OF TRANSFORMATIONAL LEADERSHIP AND EMPLOYEE COMPETENCE ON EMPLOYEE PERFORMANCE WITH INTRINSIC MOTIVATION AS A MEDIATING VARIABLE - Maringan; A Hadi Arifin; Faisal Matriadi; Dewi Kumalasari (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study examines the effect of transformational leadership and employee competence on employee performance and explores the mediating effect of intrinsic motivation variables. The sample in this study was 120 employees at Lhokseumawe Customs and Aceh Province. The analytical tool used is path analysis with a Structural Equation Modeling method using the Amos program. The results showed that each variable of transformational leadership and employee competence has a positive and significant effect on intrinsic motivation and employee performance. The inherent motivation variable mediates transformational leadership with employee performance variables in partial mediation and the intrinsic motivation variable mediates employee competence with employee performance variables in full mediation.